Effect of using crushed concrete roof tiles as coarse aggregates on properties of concrete / Manaff Mohd Ismail, Hamidah Mohd Saman and Azmi Ibrahim - Ismail, Manaff Mohd; Mohd Saman, Hamidah; Ibrahim, Azmi (2002)
The research work reported herein is to investigate the possibility of developing new materials that can be used in the production of Ordinary Portland Cement (OPC) concrete. The potential use of some recycled concrete roof tiles (CRT) as aggregates in OPC are documented in this paper. The use of CRT aggregates, in the right proportions, may provide the much-needed improvement in concrete performance and in the development of mechanical properties without substantially increasing the unit weight of the resulting mix compared with that of an equivalent conventional aggregate concrete. Tests were performed on 28-day-old specimens to determine sorptivity and compressive strength of concrete containing CRT aggregates. In general, the specimens were found to possess lower sorptivity and higher compressive strength compared with those of the control mix.